Artificial Intelligence (AI) dalam Pembelajaran Matematika: Kajian Bibliometrik: Penelitian - Rusdial Marta; Fadhilaturrahmi, Fadhilaturrahmi; Zulfah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The application of Artificial Intelligence (AI) in mathematics education offers great potential to enhance the quality of education by creating more personalized and adaptive learning experiences. This article explores the role of AI in mathematics education through a bibliometric analysis of related literature, aiming to identify research trends, key topics, and emerging international collaborations. Based on analyses using methods such as treeMap, co-occurrence network, thematic map, factorial analysis, collaboration network, and word cloud, this study highlights the dominance of AI and mathematical modeling topics, as well as the close relationship between technology, education, and computer science. While AI offers numerous opportunities to improve students' understanding of complex mathematical concepts, challenges related to technology access and educators' expertise still need to be addressed. This study also emphasizes the importance of international collaboration in accelerating the adoption and innovation of AI technology in mathematics education. The findings are expected to provide a foundation for further research on the application of AI in education, focusing on the development of more advanced and inclusive adaptive learning systems